Suitability of Self‐Reducing and Slag‐Forming Briquettes for Electric Arc Furnace Use Based on Laboratory Tests. Issue 2 (10th November 2021) - Abdelrahim, Ahmed; Aula, Matti; Iljana, Mikko; Willms, Thomas; Echterhof, Thomas; Steinlechner, Stefan; Mombelli, Davide; Mapelli, Carlo; Omran, Mamdouh; Preiss, Stefan; Fabritius, Timo
Abstract : The in‐plant recycling routes of side streams produced in electric arc furnace (EAF) steelmaking remain underexplored. Briquetting is an attractive technique to enable their recycle. Briquettes introduced into EAF must possess certain mechanical and chemical properties. However, no standard is available to determine the suitability of briquettes used in the EAF process. Herein, eight side streams are characterized, and used to produce seven different briquettes to be used in EAF. Briquettes tested consist of four self‐reducing briquettes and three slag‐forming briquettes produced using different recipes. The briquettes are subjected to several mechanical and thermal tests which reflect their intended use in EAF. The mechanical tests include compression and drop tests, and the thermal tests include optical dilatometry, thermogravimetric analysis (TGA)–derivative thermogravimetry (DTG)–mass spectrometry (MS), and full‐scale briquette reduction tests. Moreover, melting trials are performed to assess the melting behavior of selected briquettes and their interaction with slag. Suitability of briquettes characteristics is assessed based on values from the literature and against reference ferroalloys and lime stones used in one of the steel plants. Two briquettes are deemed suitable for EAF use, while three briquettes are deemed unsuitable, and two briquettes are considered of limited use. Abstract : Herein, testing techniques are used to assess the suitability of briquettes in electric arc furnace (EAF) operations. Self‐reducing and slag‐forming briquettes utilizing different binders are tested. Charging, heating, and melting behavior are assessed. Three briquettes are deemed suitable for use in EAF operations, while two briquettes are deemed of limited use, and two briquettes are deemed unsuitable.